Immunohistochemical Expression of COX2 in Urothelial Carcinoma of the urinary bladder - Shayan Khattab Omer; Jalal Ali Jalal; Zheen Othman (Advanced Medical Journal)
Background and objectives: Urothelial carcinoma of urinary bladder constitutes 90% of bladder cancer cases. Cyclo-oxygenase 2 as an immune-histochemical marker, is not expressed in normal tissues, while it is expressed in some cancers including urothelial carcinoma. The purpose of this study is detecting the frequency of expression of Cyclo-oxygenase 2 in urinary bladder’s urothelial carcinoma in association with certain clinicopathological variables.